Optimization to comprehensive evaluation of students: office to the rescue - Artur Pastor García (Centro de Estudios Financieros, 2016)
Student assessment focuses primarily on assigning grades in different subjects with educational platforms to introduce numerical grades. Some allow you to enter data absenteeism of students but still no methods that allow a comprehensive assessment of both the class and the student. Developing a tool that mitigates these limitations or supplement becomes the main objective of this work. Office automation makes available to any user immense possibilities for a comprehensive assessment of the student. A template developed interactive displays from the office can provide a tool to evaluate any subject or class statistical parameters. The template is more effective than current educational platforms criteria show statistical parameters of the class and students as well as to generate individualized reports.